P53 Phosphoinositide-3 kinase and mek inhibition prevents uptake of bacteria by airway epithelial cells. (15th November 2017) - Duffett, EC; Fenwick, PS; Barnes, PJ; Donnelly, LE
Abstract : Introduction: Bacteria are associated with COPD exacerbations with Haemophilus influenzae, and Streptococcus pneumoniae being predominant. Airway epithelium can protect pathogens from host defences and antibiotic treatment by internalisation. The mechanisms of this are unclear but may involve phosphoinositide-3- kinase (PI3K), p38, and ERK pathways. This requires many primary cells and therefore a validated cell line model would be of benefit. Therefore, we compared uptake of pathogenic bacteria by airway epithelial cells from non-smokers and COPD patients with A549 and BEAS-2B cell lines and the effects of pathway inhibitors were examined. Methods: Non-smoker (n=7) and COPD (n=8) primary airway epithelial cells, and cell lines (BEAS-2B and A549 n=5) were incubated with fluorescently-labelled, heat-killed, H. influenzae, S. pneumoniae, or E. coli for up to 72 hours and uptake fluorimetrically. Confocal microscopy was used to confirm internalisation of bacteria. CXCL8 release was measured using ELISA. Effects of pathway inhibitors were determined by pre-treating cells with increasing concentrations of LY294002 (PI3K inhibitor), VX745 (p38 inhibitor), or PD98059 (ERK pathway inhibitor). Cell viability was assessed by MTT assay. Results: Primary airway epithelial cells internalised respiratory bacteria spp. but not E. coli, in a time-dependent manner, with COPD cells internalising more H. influenzae but not S. pneumoniae compared to non-smokers at 48 hour ( H. influenzae Non-smoker: 0.97±0.23 vs . COPD: 2.49±0.7 RFU χ 10 3, p<0.05) and 72 hour ( H. influenzae Non-smoker: 1.44±0.35 vs . COPD: 3.01±2.2 RFU χ 10 3, p<0.05). A549 cells engulfed more bacteria than primary cells but the responses of BEAS-2B cells were similar to COPD cells and were used for subsequent experiments. Uptake was inhibited by LY294002 and PD98059, but not VX745. Conversely VX745, but not LY294002 or PD98059 inhibited CXCL8 release (Table 1). None of the treatments affected cell viability. Conclusion: COPD airway epithelial cells engulf more H. influenzae than cells from non-smokers and this can be modelled by BEAS-2B cells. Uptake appears to require PI3K and ERK pathways but not p38 although, p38 is required for cytokine release. These data suggest that PI3K or MEK inhibitors in combination with antibiotics might be a good therapeutic strategy to treat bacterial exacerbations and recolonisation in COPD.